2014
DOI: 10.1128/iai.01244-13
|View full text |Cite
|
Sign up to set email alerts
|

Hidden in Plain Sight: Chlamydial Gastrointestinal Infection and Its Relevance to Persistence in Human Genital Infection

Abstract: Although the concept of persistence in chlamydial infections has been recognized for about 80 years, there is still very little known about the mechanism by which this occurs. In this review, we revisit an old paradigm, long known to chlamydiologists and veterinarians, that in virtually all hosts of chlamydiae, including mammals and birds, chlamydiae reside in the gastrointestinal tract for long periods of time in the absence of clinical disease. Thus, if gastrointestinal infection occurs in most hosts, then i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
143
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(153 citation statements)
references
References 50 publications
6
143
0
4
Order By: Relevance
“…The recent finding that the genital tract C. muridarum spread to the GI tract to establish a long-lasting infection (36) further strengthens the association of the long-term pathology in the upper genital tract with the long-lasting infection in the GI tract. Some have proposed that the long-lasting infection with chlamydial organisms in the GI tract may serve as a reservoir for autoinoculation, hence enhancing chlamydial pathogenicity in the genital tract (35,37). However, this hypothesis has not been proven.…”
mentioning
confidence: 93%
“…The recent finding that the genital tract C. muridarum spread to the GI tract to establish a long-lasting infection (36) further strengthens the association of the long-term pathology in the upper genital tract with the long-lasting infection in the GI tract. Some have proposed that the long-lasting infection with chlamydial organisms in the GI tract may serve as a reservoir for autoinoculation, hence enhancing chlamydial pathogenicity in the genital tract (35,37). However, this hypothesis has not been proven.…”
mentioning
confidence: 93%
“…Recently, Yeruva et al (17) reported that C. muridarum organisms introduced into the mouse GI tract via an intragastric inoculation not only persisted in the GI tract for more than 100 days but were also more resistant to antibiotic treatment (17). These observations have led to the hypothesis that long-lasting chlamydial infection in the GI tract may serve as a reservoir for reinfecting the genital tract (18). Consistent with this hypothesis are the findings that GI tract infection with Chlamydia trachomatis has been detected not only in men having sex with men (MSM) (19,20) but also in women (21).…”
mentioning
confidence: 99%
“…The previous studies summarized above have shown that the genital C. muridarum can spread to the rest of the body, including the GI tract during the first few weeks of the infection (11)(12)(13)(14)(15), and that the orally or intragastrically inoculated C. muridarum can persist in the GI tract for long periods of time (16)(17)(18)32). It remains unknown whether the genital C. muridarum spreading to the GI tract can also lead to the long-lasting infection in the GI tract.…”
mentioning
confidence: 99%
“…64 Fifth, auto-381 inoculation in women of cervical chlamydia infection from the rectal site has been suggested 382 as a factor that could contribute to repeated detection of chlamydia in genital samples; 107 …”
mentioning
confidence: 99%